EFL Teachers Challenges in Designing Assessment Material for Students’ Listening Skills - Nurhayati, Nurhayati; Setiawaty, Puji Wahyu; Nur, Sahril (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
This study investigates the challenges EFL teachers face when designing listening assessment materials, with a focus on understanding these obstacles and identifying strategies to address them. The research aims to explore the alignment of assessment practices with student proficiency levels, resource accessibility, and the impact of time constraints on assessment quality. The study involves eight active English teachers from diverse educational institutions as participants. Data were collected using an online questionnaire designed to gather insights into teachers’ perspectives and strategies, guided by the CIPP (Context, Input, Process, Product) evaluation model. This structured framework facilitated a comprehensive analysis of contextual needs, available resources, procedural approaches, and assessment outcomes. The data were analyzed descriptively using Google Forms, with key findings highlighting significant challenges in sourcing appropriate audio materials, ensuring inclusivity and validity, and managing time for creating bespoke assessments. Results revealed that while 50% of teachers successfully aligned assessments with student abilities, 25% faced difficulties in selecting suitable materials due to resource limitations. Teachers frequently relied on self-created or freely available online resources and employed pre-made tests due to time constraints. Despite these efforts, gaps in assessment literacy and resource access persisted. The study underscores the need for professional development programs to enhance language assessment literacy, improved access to diverse, high-quality audio materials, and systemic support to address these challenges. By addressing these issues, this research contributes to more effective listening assessment practices, fostering equitable and comprehensive EFL education.